Pembinaan Hubungan Sosial Menurut Islam - Arsetya Rahmanda; Aulia Rahman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Humans are social creatures. In general, humans as social beings mean that humans cannot live alone and need other humans. In social life, of course, humans are in the midst of a society that has many differences in all respects, both individually and culturally. So the researchers tried to uncover how to create or foster social relations according to Islam based on the hadiths of the Prophet Muhammad. This research is a library research. From the research, it was found that good social relations according to Islam based on the hadith of the Prophet, can be realized by maintaining friendly relations, giving mutual benefits, mutual respect and respect, and fostering a sense of security in other individuals.